Laparoscopic Cholecystectomy in Patients with Wall-Echo-Shadow (WES) Complex in Ultrasonography: a Prospective Cross-sectional Study - Shrestha, Bhupendra Charan; Adhikari, Milan; Timsina, Aliza; Kumar Yadav, Sanjay; Pandit, Narendra (Birat Journal of Health Sciences, 2024)
Introduction: Cholelithiasis, a common gastrointestinal disorder, significantly impacts healthcare and quality of life. Laparoscopic cholecystectomy (LC) is the preferred treatment, but the significance of "Wall-Echo-Shadow” Complex on gallbladder ultrasound remains unclear. Objective: To study outcomes, intraoperative details, and complications in LC patients with WES complex. Methodology: A hospital based prospective cross-sectional study was conducted in the Department of Surgery between March 2023 to November 2023. All consecutive patients with WES complex on ultrasound, and planned for laparoscopic cholecystectomy were included. Data was collected on patient age, sex, duration of symptoms, intraoperative findings, state of gallbladder, ability of achieve critical view of safety, open conversion and postoperative complications. A non-WES complex group in the ratio of 1:2 was consecutively enrolled for the comparison of outcome using the Nassar intraoperative difficulty score. Results: Among 382 symptomatic gallstone diseases patients undergoing elective LC, 16 patients (4%) had wall echo complexes confirmed on ultrasonography. The mean age of the patients was 49.5 years, with female (62%) predominance. Eleven (68%) patients had contracted gallbladder intraoperatively. One patient (6%) required conversion to open cholecystectomy due to the failed critical view of safety achievement. One (6%) female patient had major complications. She had retained cystic duct stone and choledocholithiasis at 30th postoperative day, requiring completion cholecystectomy after endoscopic stone clearance from bile duct. Despite there being higher Nassar score grade III in non-WES group, it did not increase the conversion or complications. The histopathological reports in all patients were negative for malignancy, and were consistent with chronic calculous cholecystitis. Conclusion: Wall echo shadow complex although being an uncommon entity suggestive of chronic gallbladder condition, does not possess difficulty in LC. Keywords: Cholelithiasis, Laparoscopic Cholecystectomy, Wall Echo Shadow